2010
DOI: 10.1063/1.3528207
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the spin pumping efficiency by spin wave mode selection

Abstract: The spin pumping efficiency of standing spin wave modes in a rectangular Y3Fe5O12/Pt sample has been investigated by means of inverse spin-Hall effect (ISHE). Standing spin waves drive spin pumping, the generation of spin currents from magnetization precession, into the Pt layer which is converted into a detectable voltage due to the ISHE. We discovered that the spin pumping efficiency is significantly higher for standing surface spin waves, hybridized with thickness modes, rather than for volume spin wave mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
111
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 21 publications
6
111
0
2
Order By: Relevance
“…"Backward" waves have a frequency dispersion with a negative group velocity for some wavelengths. While these spin waves have been studied in great detail over the last decades, the effect of an adjacent normal metal on these waves has only recently been investigated.Experimentally, it has been observed that spinpumping differs for FVMSWs, BVMSWs and MSSWs and that it depends on the spin-wave wavelength [6,8,9,[12][13][14]. Recent experiments [8] have demonstrated that the magnetization dissipation is larger for surface spin waves in which the excitation amplitude is localized at the magnetic insulator-normal metal interface.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…"Backward" waves have a frequency dispersion with a negative group velocity for some wavelengths. While these spin waves have been studied in great detail over the last decades, the effect of an adjacent normal metal on these waves has only recently been investigated.Experimentally, it has been observed that spinpumping differs for FVMSWs, BVMSWs and MSSWs and that it depends on the spin-wave wavelength [6,8,9,[12][13][14]. Recent experiments [8] have demonstrated that the magnetization dissipation is larger for surface spin waves in which the excitation amplitude is localized at the magnetic insulator-normal metal interface.…”
mentioning
confidence: 99%
“…Recent experiments [8] have demonstrated that the magnetization dissipation is larger for surface spin waves in which the excitation amplitude is localized at the magnetic insulator-normal metal interface. To utilize spin-pumping from thin film magnetic insulators into adjacent normal metals, a coherent theoretical picture of these experimental findings must be developed and understood, which is the aim of our work.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently C. W. Sandweg et al [14] carried out studies of spin pumping efficiency across the YIG/Pt interface using the inverse spin-Hall effect (ISHE). In these studies, the dc voltage was measured across the Pt layer for different rf excitation modes.…”
mentioning
confidence: 99%